Emotion regulation and attachment: Relationships with children’s secure base, during different situational and social contexts in naturalistic settings - Roque, Lisa (2013)
This study investigated the relationships between children’s secure base and emotion regulation, namely their behavioral strategies and emotional expressiveness, during different situational and social contexts in naturalistic settings. Fifty-five children ranging in age from 18 to 26 months of age and their mothers participated in this study. Children were exposed to three situational (fear, positive affect and frustration/anger) and two social (maternal constraint and involvement) contexts. Toddlers’ behavioral strategies differed as function of emotion-eliciting context, maternal involvement and attachment quality. Emotional expressiveness varied as function of an interaction involving situational contexts, maternal involvement and children’s attachment security.